2015
DOI: 10.1039/c4cp04862h
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigations of the thermodynamic properties of size-selected water and Ar–water clusters: high-pressure transitions

Abstract: Classical parallel-tempering Monte Carlo simulations in the isothermal-isobaric ensemble were carried out for the (H2O)20 and Ar(H2O)20 clusters, over a wide range of temperatures (30-1000 K) and pressures (3 kPa-10 GPa) in order to study their thermodynamic properties and structural changes. The TIP4P/ice water model is employed for the water-water interactions, while both semiempirical and ab initio-based potentials are used to model the interaction between the rare-gas atoms and the water molecules. Tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…[39] and references therein). Nowadays, most of the molecular dynamics (MD) simulations still rely on empirical or semiempirical force fields as an important tool for investigating processes, such as the nucleation, growth, structural organization, and cage occupancy of clathrate hydrates, as well as the dissolution of the guest gas in water, [40][41][42][43][44][45][46][47][48][49][50] whereas for ab initio simulations, issues such as computational efficiency,s ystem-size scaling, and accurate electronic structuret reatments are of importance,w ith density functional theory (DFT) approaches [36,38,[51][52][53][54][55] being, more recently,a lso valuable in studyings uch inclusion compounds. In this vein, energy benchmarksf rom accurate quantum-mechanical calculations are essential for testing both force fields and DFT methods.…”
Section: Introductionmentioning
confidence: 99%
“…[39] and references therein). Nowadays, most of the molecular dynamics (MD) simulations still rely on empirical or semiempirical force fields as an important tool for investigating processes, such as the nucleation, growth, structural organization, and cage occupancy of clathrate hydrates, as well as the dissolution of the guest gas in water, [40][41][42][43][44][45][46][47][48][49][50] whereas for ab initio simulations, issues such as computational efficiency,s ystem-size scaling, and accurate electronic structuret reatments are of importance,w ith density functional theory (DFT) approaches [36,38,[51][52][53][54][55] being, more recently,a lso valuable in studyings uch inclusion compounds. In this vein, energy benchmarksf rom accurate quantum-mechanical calculations are essential for testing both force fields and DFT methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Such nanoconfined systems have been the topic of broad research, focused on their different chemical and physical behavior compared with the bulk systems, as the confined molecules are subject to surrounding host medium, resulting specific unexpected effects on properties and dynamics of the guest moieties. So far, various types of nanocavities have been investigated, such as those of clathrate hydrates, [6][7][8][9][10][11][12][13][14][15] rare gas nanodroplets, [16][17][18][19][20][21] fullerenes, 22 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, from the theoretical perspective, the investigations are still ongoing towards the development of fundamental physico-chemical processes in clathrate exploitation, including their microscopic structural evolution, aiming to gain a better understanding of stabilities and storage capacities of their cavities. 2,[8][9][10] The rapid increase in computing power has also led to numerous quantum chemistry calculations on guest-host interactions, as well as a plethora of benchmark computations in large water clusters. [11][12][13][14][15][16][17][18][19][20][21] The results of such studies have shown that ab initio electronic structure methods provide independent and accurate means of reaching a good understanding of the nature of hydrates and description of the underlying guest-host potential.…”
Section: Introductionmentioning
confidence: 99%